5x-9-2x+3=90

Simple and best practice solution for 5x-9-2x+3=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-9-2x+3=90 equation:


Simplifying
5x + -9 + -2x + 3 = 90

Reorder the terms:
-9 + 3 + 5x + -2x = 90

Combine like terms: -9 + 3 = -6
-6 + 5x + -2x = 90

Combine like terms: 5x + -2x = 3x
-6 + 3x = 90

Solving
-6 + 3x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 3x = 90 + 6

Combine like terms: -6 + 6 = 0
0 + 3x = 90 + 6
3x = 90 + 6

Combine like terms: 90 + 6 = 96
3x = 96

Divide each side by '3'.
x = 32

Simplifying
x = 32

See similar equations:

| h=-4.9t^2+12t | | -8x^2-30x-25=0 | | 262+n=528 | | 3t-(t+7)=11 | | 107.06=0.13x+3.06 | | 4x-6=28 | | 161+n=451 | | 6x+25-4x+25=-2 | | y=0.13(107.06)+3.06 | | 9u+4=6u+28 | | 4-1(x+1)=8 | | 4c+27=2c+57 | | (x+30)+x*2=180 | | 4-.33(x-9)=-1 | | 7y+5=3y-11 | | 4.8x+9.6=19.2 | | 3(x+5)-6x=-18 | | 169y^4-1=0 | | 4x-13+2x+19=90 | | 23+h-3.1=27 | | y=0.16(700)+17.93 | | 7x^2+(-6xy)+x+(-8)= | | x+5=4x+6 | | c=78349737+797349.3289x | | 5x-9+2x+3=90 | | 2x+16x=.40x | | 700=0.16x+17.93 | | 3x-4(9)=-19 | | 2p+7q-6(2p-9q+2r)= | | y=4(16)+45 | | 12.6-1x=2x | | 34+y=47+29 |

Equations solver categories